Aspirin-Dipyridamole Prophylaxis of Sickle Cell Disease Pain Crises - Chaplin, H, Jr.; Alkjaersig, N; Fletcher, A P; Michael, J M; Joist, J H (Thrombosis and Haemostasis, 1980)
We have previously reported that long term daily administration of aspirin-dipyridamole significantly improved laboratory findings indicative of disease activity in patients with sickle-cell disease. The laboratory index most influenced by platelet inhibitory drug therapy was the plasma concentration of high molecular weight fibrin(ogen) complexes (HMWFC), a moiety which reflects the rate of fibrin formation in vivo. Although improvement of laboratory findings with therapy was accompanied by apparent clinical improvement, the limited clinical data then available did not reach statistical significance.This report describes extension of the trial of prophylactic platelet inhibitory drug therapy. Three patients were studied during a two year period on daily aspirin-dipyridamole therapy and during a two year control period. Plasma fibrinogen concentration was correlated with patient clinical status and the clinical findings suggested that the treatment was of modest prophylactic efficacy.In 1976, we reported a characteristic pattern of blood coagulation abnormalities accompanying painful musculoskeletal sickle-cell disease (SSD) crises (1,2). With the onset of crisis, there was an increase in plasma high molecular weight fibrin(ogen) complexes (HMWFC) and a transient fall in platelets and in plasma Factor XIII. Subsequently, plasma fibrinogen concentration rose (peak at 1 week after onset of symptoms), platelets rose (peak at 2 weeks) and plasma Factor XIII increased (peak at 3 weeks). Subsidence of crisis was associated with a fall in HMWFC and a subsequent increase in fibrinogen first derivative, which reflects the rate of fibrinogenolysis. Plasma HMWFC concentration reflects the rate of fibrin formation in vivo (3) and plasma Factor XIII concentration decreases with intravascular fibrin deposition (4). Thus these laboratory findings support the hypothesis that in the early stages of SSD crisis, fibrin deposition and/or thrombosis significantly enhance the role of sickled erythrocytes in producing vascular occlusion and/or organ infarction.We also reported that, over extended periods of observation, hemostatic findings and patient clinical status were generally correlated. Except for persistent depression of plasma Factor XIII concentration, laboratory findings during asymptomatic periods were essentially normal. Emphasis was placed on the value of hemostatic measurements as objective documentation of clinical status, and both laboratory and preliminary clinical observations were reported in three patients during a control period and during daily aspirin-dipyridamole therapy. Aspirin-dipyridamole therapy significantly improved laboratory measures of disease activity, particularly mean plasma HMWFC concentration, but insufficient data was obtained to determine whether the treatment was of clinical value.We have now observed each of the three patients at weekly intervals for a minimum of 104 weeks on daily aspirin-dipyridamole, followed by a minimum of 104 weeks off the antiplatelet prophylactic regimen. This report compares clinical and laboratory findings during platelet inhibitory drug administration and following its discontinuation. Plasma fibrinogen measurements correlated with patient clinical status and the clinical findings suggest that the treatment was of modest prophylactic benefit.
Keywords: Sickle cell disease; Fibrinogen catabolism; Anti-platelet drug therapy